SOCIO ECONOMIC FACTORS AFFECTING BEAN PRODUCTION IN NORTHERN UGANDA - A. O, Tekkara; A, Kumakech; G, Otim; A, Alexandrina; S, Wamani; L, Turyagyenda (JOURNAL OF ADVANCES IN AGRICULTURE, 2017)
Beans is an important source of proteins and income for poor resource households. However the yied of beans has remained very low in comparion to yields obtained under ideal management conditions. This necessitated the examination of socio-economic factors influencing bean yields of smallholder farmers in eight districts of northern Uganda. A total of 1112 farmers were randomly selected from the study area and the data was subjected to descriptive statistics and regression analysis using IBM SPSS (version 20). The results indicated that 2.3% of variation in beans yield was attributed to amount of seed and acreage planted. The study further revealed that majority of the respondents (81.7%) were practicing farming and most of them were 31-40 years of age (31%). Also, 90.4% and 59.6% of the respondents had bean gardens ranging from 1 to 2 acres and sourced seeds for planting from local market respectively. While 90.4% of the farmers didn’t have access to credit, 91.7% actually had access to market information. From the study, majority of the farmers (20.4%) attained yields of either 60 - 120kgs or above 240kgs per acre. It is recommended that, the governmentâ€™s effort to support agricultural mechanization for increased acreage and productivity be strengthened through private public partnership to quickly reach the smallholder farmers.